An Easy-to-Use Protocol for Segmenting and 3-D Printing Craniofacial CT-Images Using Open-Source Software. Issue 1 (March 2022) - Pakvasa, Mikhail; Prescher, Hannes; Hendren-Santiago, Bryce; Da Lomba, Tony; McKenzie, Nicholas; Orsbon, Courtney; Collier, Zachary; Ramirez-Garcia, Richard; Gomez, Isabella; Reid, Russell R.
Introduction: Stereolithography, also known as 3D printing (3DP), is a versatile and useful technology with many healthcare applications. While 3DP has gained tremendous popularity, it remains a daunting and perceptibly time-consuming process for the inexperienced user, with most turning to commercially printed products. Commercial vendors are expensive. We propose that 3DP is feasible for the inexperienced user with the appropriate knowledge and tools. Methods: A 3DP protocol was created for model design and printing using open-source software and a low-cost desktop printer. It was betatested by 3 inexperienced users. The fidelity of the protocol was then tested in direct comparison to industry models made for 3 patients undergoing mandibular distraction osteogenesis, using standard cephalometric measurements. Results: All inexperienced testers were able to successfully create a 3D model using the easy-to-follow protocol without the use of any other resources. The models were created in a mean time of 170 minutes. All cephalometric measurements on the open-source printed models were equal to within 0.5 to 1.0 mm of the respective industry models. Conclusions: As the 3DP process is simplified and desktop printers and materials become more affordable, we anticipate that its implementation will become more commonplace. We describe a step-by-step, protocol using open-source software and affordable materials to create 3D models.